Psychosocial interventions for people who self-harm: methodological issues involved in trials to evaluate effectiveness - Witt, K; Townsend, E; Arensman, E; Gunnell, D; Hazell, P; Sailsbury, T; Van Heeringen, K; Hawton, K (Routledge, 2019)
OBJECTIVE:We have assessed the methodological quality of randomized controlled trials (RCTs) of interventions to prevent self-harm repetition and suicide. METHODS:Trials were identified in two systematic reviews of RCTs of psychosocial treatments following a recent (within six months) episode of self-harm indexed in any of five electronic databases (CCDANCTR-Studies and References, CENTRAL, Medline, Embase, and PsycINFO) between 1 January, 1998 and 29 April, 2015. RESULTS:A total of 66 trials were included, 55 in adults and 11 in children and adolescents. While evidence for efficacy of some approaches has grown, there were few trials from low-to-middle income countries, little information on interventions for males, information on the control condition was often limited, data on suicides were often not reported, and, while trials have increased in size in recent years, most have included too few participants to detect clinically significant results. CONCLUSIONS:There are major limitations in many trials of interventions for individuals who self-harm. Improved methodology, especially with regard to study size, provision of details of control therapy, and evaluation of key outcomes, would enhance the evidence base for clinicians and service users.